Efficient desulfurization of light crude oil using MOF and its composite - Goyal Sonali; Kukretee Nupur; Nayak Arunima; Bhushan Brij (E3S Web of Conferences)
High sulfur content in petroleum fuels is a critical concern due to its significant contribution to environmental pollution through the formation of sulfur oxides during combustion. These sulfur compound not only degrade the quality of the fuel and quantity of finished petrochemical products, but also adversely affect the environment and damage equipment, tanks and pipelines. To address these issues and meet the rising need for both cleaner fuels and high-valued petrochemical products, desulphurization has become a key focus in crude oil refining. In this study, a MOF composite, ZIF-8/Co with montmorillonite clay was fabricated and tested for the desulfurization of light crude oil (LCO). For the first time, this composite adsorbent was applied to real crude oil system, achieving an impressive sulfur removal efficiency of 58.9%. The use of a green synthesis method further emphasizes the sustainability and cost effectiveness of this approach, presenting a promising advancement in crude oil desulfurization technology.